2009
DOI: 10.1371/journal.pone.0005120
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Functional, Gene Expression and Genomic Analysis for the Identification of Cancer Targets

Abstract: The majority of new drug approvals for cancer are based on existing therapeutic targets. One approach to the identification of novel targets is to perform high-throughput RNA interference (RNAi) cellular viability screens. We describe a novel approach combining RNAi screening in multiple cell lines with gene expression and genomic profiling to identify novel cancer targets. We performed parallel RNAi screens in multiple cancer cell lines to identify genes that are essential for viability in some cell lines but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
97
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 37 publications
9
97
0
Order By: Relevance
“…However, the potential therapeutic effects of WEE1 inhibition in the absence of chemotherapies have not been widely explored. RNA interference knockdown of WEE1 is known to inhibit proliferation of cancer cell lines (13,33), and more recently, it was shown that MK-1775 alone can induce apoptosis in sarcoma cell lines treated in vitro (34). Our results similarly highlight a requirement for WEE1 activity to maintain cellular viability and genomic stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the potential therapeutic effects of WEE1 inhibition in the absence of chemotherapies have not been widely explored. RNA interference knockdown of WEE1 is known to inhibit proliferation of cancer cell lines (13,33), and more recently, it was shown that MK-1775 alone can induce apoptosis in sarcoma cell lines treated in vitro (34). Our results similarly highlight a requirement for WEE1 activity to maintain cellular viability and genomic stability.…”
Section: Discussionmentioning
confidence: 99%
“…High expression of WEE1 was found in malignant melanoma and correlated with poor disease-free survival in this population (11). Aberrant WEE1 expression has been implicated in additional tumor types such as hepatocellular carcinoma (12), breast cancer (13), colon carcinoma (14), lung carcinoma (15), and head and neck squamous cell carcinoma (16). Advanced tumors with an increased level of genomic instability may require functional checkpoints to allow the repair of DNA perturbations that accompany genomic instability.…”
Section: Introductionmentioning
confidence: 95%
“…Microarray analysis of experimental samples, such as gene-transfected cells, has led to identification of valuable molecular markers involved in tumor proliferation, angiogenesis, prognosis and therapeutic response (Duggan et al, 1999;Quackenbush, 2006;Perez-Diez et al, 2007;Iorns et al, 2009). Thus, we used a global cDNA microarray to identify downstream target genes of IRX1.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, WEE1 is overexpressed in human glioblastoma and a subset of breast cancers (Iorns et al, 2009;Mir et al, 2010), and CHK1 mRNA expression was elevated in MYC-amplified neuroblastoma (Cole et al, 2010). The mechanism behind upregulation of CHK1 in MYC-amplified neuroblastoma is not known (Cole et al, 2010).…”
Section: Overexpression Of Wee1 and Chk1 In Human Cancermentioning
confidence: 99%